2019
DOI: 10.1108/hff-10-2018-0595
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of flow in incompressible regenerative turbo-machines with bucket form blades based on the geometry of flow path

Abstract: Purpose Regenerative flow pumps are dynamic machines with the ability to develop high heads at low flow rates. Simplicity, compactness, stable features and low manufacturing costs make them interesting for many applications in industries. The purpose of this study is to present a new method for calculating the flow through regenerative pumps with bucket form blades to predict the performance curves by a cheap and easy-to-use way. Design/methodology/approach The analysis was carried out based on the geometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…No parametric studies involving the stripper angle have been carried out for doubleside vane impeller machines. For pumps, Badami and Mura [13] used 311 • , Maity et al [35] used 316 • , and an angle of 344 • was used by [23][24][25][26]. For hydrogen and air compressors, Badami and Mura [14] used an angle of 340 • , whereas, for helium, they used 270 • .…”
Section: Stripper Angle (θ S )mentioning
confidence: 99%
See 1 more Smart Citation
“…No parametric studies involving the stripper angle have been carried out for doubleside vane impeller machines. For pumps, Badami and Mura [13] used 311 • , Maity et al [35] used 316 • , and an angle of 344 • was used by [23][24][25][26]. For hydrogen and air compressors, Badami and Mura [14] used an angle of 340 • , whereas, for helium, they used 270 • .…”
Section: Stripper Angle (θ S )mentioning
confidence: 99%
“…They considered symmetric as well as asymmetric vanes. Nejadali [23] presented an easy and novel method to compute flow in a pump with a bucket shape vane. Nejad et al [24] conducted experiments and found out the best vane angle (10 • ) for a pump.…”
Section: Introductionmentioning
confidence: 99%
“…As a general practice, CFD studies are validated by experimental results. However, Nejadali 60 developed an analytical method to compute the flow characteristics in a Regenerative Flow Pump (RFP). He treated the fluid flow trajectory as helical and wrapped in a Taurus.…”
Section: Types Of Models and Studiesmentioning
confidence: 99%